Evaluation of arm-leg coordination in flat breaststroke - Chollet, D.; Seifert, L.; Leblanc, H.; Boulesteix, L.; Carter, M. (International Journal of Sports Medicine, 2004)
This study proposes a new method to evaluate arm-leg coordination in flat breaststroke. Five arm and leg stroke phases were defined with a velocity-video system. Five time gaps quantified the time between arm and leg actions during three paces of a race (200 m, 100 m and 50 m) in 16 top level swimmers. Based on these time gaps, effective glide, effective propulsion, effective leg insweep and effective recovery were used to identify the different stroke phases of the body. A faster pace corresponded to increased stroke rate, decreased stroke length, increased propulsive phases, shorter glide phases, and a shorter T1 time gap, which measured the effective body glide. The top level swimmers showed short time gaps (T2, T3, T4, measuring the timing of arm-leg recoveries), which reflected the continuity in arm and leg actions. The measurement of these time gaps thus provides a pertinent evaluation of swimmers' skill in adapting their arm-leg coordination to biomechanical constraints.